Psychoanalytical fundamentals in the construction of subjectivity in Psychosis (Research, Society and Development, 2021)
This research work on the theme of psychosis follows a psychoanalytic line of studies, with a qualitative character of narrative bibliographic review. The same investigates the foundations of the clinic of psychoses, bringing a study of the Schreber case made by Freud, as the reading of scholars who reviewed his works in order to better understand their consequences. Another objective is to verify the dimension of transference linked to clinical management, which concerns the analyst-patient relationship, as another guiding principle for the treatment of psychosis. It is known that transference is part of both clinical neurosis and psychosis. But it is in the clinic of psychosis that Freud claims that it is negative. This “obscuration” by this word used by Freud is what will lead many psychoanalysts to focus on this theme. About handling, between the lines of the Schreber case, Freud gives some indications. However, significant advances come in the works of post-Freudian authors interested in breaking into the “dry” terrain of psychoses. Considering the sum of these themes, the possibility of treatment for these patients is perceived, as a renewed knowledge about the subject of madness. Here, the "crazy", the psychotic, as a subject in his, in "our" history, in order to ensure a place of his own - not for the sake of a state of "sanity", whose society grants him as fair, but for what is rightfully his.